2019
DOI: 10.1371/journal.pone.0223039
|View full text |Cite
|
Sign up to set email alerts
|

Female rats release a trapped cagemate following shaping of the door opening response: Opening latency when the restrainer was baited with food, was empty, or contained a cagemate

Abstract: Research on pro-social rat behaviour is growing within the fields of comparative psychology and social neuroscience. However, much work remains on mapping important variables influencing this behaviour, and there is even disagreement on whether this behaviour is empathetically motivated and correctly labelled pro-social, or whether the behaviour is motivated by social contact. The present study used the helping behaviour paradigm where a rat can release a familiar cagemate from a restrainer. Prior to testing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…When food motivation was high (restricted access to food outside the session), however, rats clearly preferred food over social release (Conditions 1-3). This finding is consistent with the Hiura et al (2018) findings, showing strong and reliable preference for food over social release when food is restricted outside the session (see also Blystad et al, 2019). Taken as a whole, the presents results show that relative preference between social and food is not invariant, but rather, is subject to reward and motivational variables (food quantity and overall food access).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When food motivation was high (restricted access to food outside the session), however, rats clearly preferred food over social release (Conditions 1-3). This finding is consistent with the Hiura et al (2018) findings, showing strong and reliable preference for food over social release when food is restricted outside the session (see also Blystad et al, 2019). Taken as a whole, the presents results show that relative preference between social and food is not invariant, but rather, is subject to reward and motivational variables (food quantity and overall food access).…”
Section: Discussionsupporting
confidence: 92%
“…Most of the rats (17 of 23) learned to open the restraint after an average of about seven sessions. Subsequent studies have verified that rats will, under a variety of conditions, respond in ways that release a rat from a restraint (Ben-Ami Bartal et al, 2014;Silberberg et al, 2014;Sato et al, 2015;Schwartz et al, 2017;Hachiga et al, 2018;Hiura et al, 2018;Blystad et al, 2019;Vanderhooft et al, 2019). The basic effect is reliable, having been replicated across different procedures and laboratories, but its core mechanisms remain a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…When food motivation was high (restricted access to food outside the session), however, rats clearly preferred food over social release (Conditions 1-3). This finding is consistent with the Hiura et al (2018) findings, showing strong and reliable preference for food over social release when food is restricted outside the session (see also Blystad et al, 2019). Taken as a whole, the presents results show that relative preference between social and food is not invariant, but rather, is subject to reward and motivational variables (food quantity and overall food access).…”
Section: Discussionsupporting
confidence: 90%
“…However, as with dogs, task ability may heavily constrain rescue behavior in rats. Indeed, when trained to open the apparatus in advance of testing, all rats released their trapped cage-mate within the first few trials [52]. Therefore, future studies in which dogs are trained to open the apparatus prior to testing are needed to facilitate further interspecific comparisons.…”
Section: Comparisons To Ratsmentioning
confidence: 99%
“…Using a simultaneous choice paradigm, Ben-Ami Bartal et al [45] showed that rats may find the act of rescuing their cage-mates to be nearly as rewarding as retrieving food treats, and may choose to share food after rescuing cage mates. However, Blystad et al [52] found that rats waited longer to open the restrainer apparatus and did so less frequently for a trapped cage-mate than for food. In contrast, dogs were as likely to rescue their owner as to retrieve treats.…”
Section: Comparisons To Ratsmentioning
confidence: 99%